Python Essentials for AWS Cloud Developers Run and Deploy Cloud-Based Python Applications Using AWS - Sakinmaz, Serkan (Packt Publishing, Limited, 2023)
A comprehensive guide to implementing Python applications in AWS while learning about key AWS services Purchase of the print or Kindle book includes a free PDF eBook Key Features Gain hands-on experience in AWS services to effectively implement Python programming Utilize Python with open source libraries to develop data pipelines, APIs, and database applications Leverage the power of AWS to create a cloud-based server and use monitoring and logging features Book Description AWS provides a vast variety of services for implementing Python applications, which can pose a challenge for those without an AWS background. This book addresses one of the more predominant problems of choosing the right service and stepping into the implementation of exciting Python apps using AWS. The book begins by showing you how to install Python and create an AWS account, before helping you explore AWS Lambda, EC2, Elastic Beanstalk, and S3 for Python programming. You'll then gain hands-on experience in using these services to build the Python application. As you advance, you'll discover how to debug Python apps using PyCharm, and then start deploying the Python applications on Elastic Beanstalk. You'll also learn how to monitor Python applications using the CloudWatch service, along with creating and publishing APIs on AWS to access the Python application. The concluding chapters will help you get to grips with storing unstructured and semi-structured data using NoSQL and DynamoDB, as well as advance your knowledge using the Glue serverless data integration service in AWS. By the end of this Python book, you'll be able to take your application development skills up a notch with AWS services and advance in your career. What you will learn Understand the fundamentals of AWS services for Python programming Find out how to configure AWS services to build Python applications Run and deploy Python applications using Lambda, EC2, and Elastic Beanstalk Provision EC2 servers on AWS and run Python applications Debug and monitor Python applications using PyCharm and CloudWatch Understand database operations on AWS by learning about DynamoDB and RDS Explore the API gateway service on AWS using Python to grasp API programming Who this book is for This book is for cloud developers, software developers, and IT specialists who want to develop Python applications on AWS as well as learn the concepts underlying AWS services for implementing the applications. Experience in Python programming is needed to be able to implement the applications on AWS.